Site-targeted complement inhibition by a complement receptor 2-conjugated inhibitor (mTT30) ameliorates post-injury neuropathology in mouse brains. (23rd March 2016) - Rich, Megan C.; Keene, Chesleigh N.; Neher, Miriam D.; Johnson, Krista; Yu, Zhao-Xue; Ganivet, Antoine; Holers, V. Michael; Stahel, Philip F.
Highlights: Post-injury complement activation leads to adverse outcomes after severe TBI. There is no pharmacological agent on the market to prevent secondary brain injury. Site-targeted CR2-conjugated complement inhibitors are novel therapeutics. CR2-fH has been shown to reduce neuroinflammation in autoimmune CNS disorders. We show that site-targeted complement inhibition is protective in experimental TBI. Abstract: Intracerebral complement activation after severe traumatic brain injury (TBI) leads to a cascade of neuroinflammatory pathological sequelae that propagate host-mediated secondary brain injury and adverse outcomes. There are currently no specific pharmacological agents on the market to prevent or mitigate the development of secondary cerebral insults after TBI. A novel chimeric CR2-fH compound (mTT30) provides targeted inhibition of the alternative complement pathway at the site of tissue injury. This experimental study was designed to test the neuroprotective effects of mTT30 in a mouse model of closed head injury. The administration of 500 μg mTT30 i.v. at 1 h, 4 h and 24 h after head injury attenuated complement C3 deposition in injured brains, reduced the extent of neuronal cell death, and decreased post-injury microglial activation, compared to vehicle-injected placebo controls. These data imply that site-targeted alternative pathway complement inhibition may represent a new promising therapeutic avenue for the future management of severe TBI.